THE INFLUENCE OF PARTICIPATION IN STUDENT ORGANIZATIONS ON SOFT SKILLS AND EMPLOYABILITY OF MANAGEMENT STUDENTS AT TADULAKO UNIVERSITY - Muh. Dani Faidil; Niluh Putu Evvy Rossanty; Lina Mahardiana; Muh. Riswandi Palawa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines how student participation in campus organizations influences soft skills and employability among Management students at Tadulako University. A survey of 103 students from the 2021 and 2022 cohorts was analyzed using SEM-PLS in SmartPLS 4. Findings reveal that organizational participation significantly improves intrapersonal and interpersonal skills, both of which positively affect employability. The direct impact of participation on employability is relatively small, but interpersonal skills emerge as the stronger mediator compared to intrapersonal skills. These results confirm that student organizations serve as strategic platforms for non-formal learning that strengthens soft skills and work readiness. The study highlights the importance of institutional support for student organizations and suggests that future research should explore additional factors, such as internship and digital literacy, to broaden employability assessment.